2005
DOI: 10.2486/indhealth.43.542
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Manual Dexterity and Neuromuscular Dysfunction in Patients with Hand-Arm Vibration Syndrome

Abstract: Manual dexterity and hand functional difficulties in daily life in hand-arm vibration syndrome (HAVS) were investigated in 29 male patients with HAVS and 30 male controls without occupational exposure to hand-arm vibration. Manual dexterity was assessed by measuring the performance time of picking up and transferring 30 red beans, one by one, from one plate to another. Vibrotactile perception thresholds at 125 Hz and grip strength were also examined. Hand functional difficulties in daily life were surveyed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
2
16
1
Order By: Relevance
“…Our findings are consistent with the results reported in other studies (6,7,21,22) which found impairment to manual dexterity in groups of workers exposed to hand transmitted vibration. However, our findings could not be directly compared with these results as most of the published studies deal with developed HAVS cases (6,7,31), rarely discussing the biological processes of damage/repair that are relevant for the The decreased grip strength has also been reported (6,8,9).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Our findings are consistent with the results reported in other studies (6,7,21,22) which found impairment to manual dexterity in groups of workers exposed to hand transmitted vibration. However, our findings could not be directly compared with these results as most of the published studies deal with developed HAVS cases (6,7,31), rarely discussing the biological processes of damage/repair that are relevant for the The decreased grip strength has also been reported (6,8,9).…”
Section: Discussionsupporting
confidence: 83%
“…Manual dexterity loss is a known consequence of vibration exposure (6,7,21,22). It results from (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations